Effect of aerobic and resistance exercise on the mitochondrial peptide MOTS-c in Hispanic and Non-Hispanic White breast cancer survivors - Christina M. Dieli-Conwright (Nature Portfolio, 2021)
Abstract MOTS-c is a mitochondrial derived peptide with exercise mimetic activity that elicits beneficial effects on metabolism and exercise capacity. Furthermore, MOTS-c effects in humans are affected by race, potentially via ethnic-specific mtDNA variations. Women treated for breast cancer are at an increased risk for cardiovascular disease, diabetes and obesity, due to side effects of cancer-treatments. We conducted a secondary analysis of the effects of a 16-week aerobic and resistance exercise intervention on MOTS-c in Hispanic and Non-Hispanic White breast cancer survivors (BCS). BCS (Stage I–III) were randomized to exercise or standard care. The intervention promoted aerobic and resistance exercise for 16 weeks. MOTS-c was analyzed in fasting plasma using an in-house ELISA. Within and between group differences were assessed by paired t-test and repeated measures ANOVA. Pearson’s correlation was computed to assess the association between MOTS-c and metabolic biomarkers at baseline and post-exercise. Twenty-five Hispanic-BCS and 24 non-Hispanic White BCS were included. Hispanic BCS were younger, of greater adiposity, had higher stage cancers, and had worse metabolic profiles at baseline compared to non-Hispanic White BCS (p < 0.001). Post-exercise, MOTS-c levels significantly increased when compared to baseline and the usual care group among non-Hispanic White BCS (p < 0.01) but not among Hispanic breast cancer survivors (p > 0.01). Post-exercise levels of MOTS-c among non-Hispanic White BCS were significantly associated with reductions in fat mass, body weight, HOMA-IR, CRP, and an increase in lean mass (p < 0.01). A 16-week aerobic and resistance intervention increased MOTS-c levels among non-Hispanic White BCS. Trial registration: This trial is registered on ClinicalTrials.gov: NCT01140282 as of June 9, 2010. https://clinicaltrials.gov/ct2/show/NCT01140282 .